Characterisation of peri-implantation endometrial Treg and identification of an altered phenotype in recurrent pregnancy loss - Granne, I; Shen, M; Rodriguez Caro, H; Chadha, G; O'Donnell, E; Brosens, J; Quenby, S; Child, T; Southcombe, J (Springer Nature, 2021)
Recurrent Pregnancy Loss (RPL) affects 2–4% of couples, and with increasing numbers of pregnancy losses the risk of miscarrying a euploid pregnancy is increased, suggesting RPL is a pathology distinct from sporadic miscarriage that is due largely to lethal embryonic aneuploidy. There are a number of conditions associated with RPL including unspecified “immune” pathologies; one of the strongest candidates for dysregulation remains T regulatory cells as depletion in the very early stages of pregnancy in mice leads to pregnancy loss. Human endometrial Treg and conventional CD4T cells were isolated during the peri-implantation period of the menstrual cycle in normal women. We identified an endometrial Treg transcriptomic signature and validated an enhanced regulatory phenotype compared to peripheral blood Treg. Parous women had an altered endometrial Treg transcriptome compared to nulliparity, indicating acquired immune memory of pregnancy within the Treg population, by comparison endometrial conventional CD4T cells were not altered. We compared primary and secondary RPL to nulliparous or parous controls respectively. Both RPL subgroups displayed differentially expressed Treg gene transcriptomes compared to controls. We found increased cell surface S1PR1 and decreased TIGIT protein expression by Treg in primary RPL, confirming the presence of altered Treg in the peri-implantation RPL endometrium.